Sad birds still fly - Tapay, Charissa Isabel Baluya (Nanyang Technological University, 2024)
Sad Birds Still Fly is a documentary that aims to portray the captivating world of local and migratory birds in Singapore, exploring their beauty and challenges faced due to increased urbanisation. Presented in the format of a radio podcast, complete with bird calls and ambient sounds, Sad Birds Still Fly immerses viewers in the spaces around Singapore that these birds call home. Through our collaboration with bird photographers, ecological experts, and ornithologists, the film highlights issues such as bird collisions, deforestation and the threat of extinction. It also offers a message of hope for the future of our environment if we work to protect and coexist with nature and wildlife.